2014
DOI: 10.1071/en14123
|View full text |Cite
|
Sign up to set email alerts
|

Antimony leaching from contaminated soil under manganese- and iron-reducing conditions: column experiments

Abstract: Environmental context. Contamination of shooting range soils by antimony (Sb) released from corroding ammunition has become an issue of public environmental concern. Because many of these sites are subject to waterlogging and consequently limited aeration, we performed column experiments with contaminated shooting range soil to investigate Sb mobility under such conditions. The results are important for our understanding of the risks arising from Sb-contaminated soils, and also for the derivation of appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…However, as the magnitude of Fe(III) reduction increases (i.e., above ~6%), Sb is subsequently released due to more extensive dissolution of Fe(III) oxide host phases and via increased competitive desorption from HCO 3 − produced via Fe(III) reduction. This complex biphasic trend (initial Sb retention, followed by Sb release) as reducing conditions develop is consistent with the result of Hockmann, Tandy, et al (2014), who found Sb mobilization occurred under reducing conditions via (1) initial reduction of Sb(V) producing Sb(III), which was first scavenged by Fe(III) oxides, and then (2) slow liberation of the newly produced Sb(III) when Eh further decreased to enable extensive reductive dissolution of Fe(III) oxides.…”
Section: Resultssupporting
confidence: 92%
“…However, as the magnitude of Fe(III) reduction increases (i.e., above ~6%), Sb is subsequently released due to more extensive dissolution of Fe(III) oxide host phases and via increased competitive desorption from HCO 3 − produced via Fe(III) reduction. This complex biphasic trend (initial Sb retention, followed by Sb release) as reducing conditions develop is consistent with the result of Hockmann, Tandy, et al (2014), who found Sb mobilization occurred under reducing conditions via (1) initial reduction of Sb(V) producing Sb(III), which was first scavenged by Fe(III) oxides, and then (2) slow liberation of the newly produced Sb(III) when Eh further decreased to enable extensive reductive dissolution of Fe(III) oxides.…”
Section: Resultssupporting
confidence: 92%
“…As a consequence, there is very little tendency for Fe atom exchange with the aqueous phase, and, as a result, goethite recrystallization is exceptionally slow under such conditions . Reducing conditions, however, are common in waterlogged soils, benthic sediments, and shallow groundwater systems. , ,,, Reducing conditions also commonly occur within anoxic microenvironments in otherwise oxic systems (e.g., within the aggregate structure of upland soils) . Under reducing conditions, Fe­(III) within minerals such as goethite can act as a terminal electron acceptor in microbial respiration, thereby leading to the generation of aqueous Fe­(II) …”
Section: Discussionmentioning
confidence: 99%
“…Antimony is a toxic and carcinogenic metalloid, and its release into the environment threatens soil and water quality, ecosystem processes, and human health. Particularly severe environmental contamination has been reported in relation to Sb mining and ore-processing activities. Antimony is also released during mining of many other metals (e.g., copper, gold, lead, and zinc) due to its common enrichment in metal sulfide ores. Other major sources of Sb release to the environment include shooting range soils (leaching of Sb during weathering of bullets) and disposal of plastic waste (especially Sb-rich E-waste such as computer plastics and consumer electronics). ,, …”
Section: Introductionmentioning
confidence: 99%
“…due to waterlogging, is typically associated with mobilisation of As, however exceptions and reverse trends have been documented (Frohne et al, 2011;Hamon et al, 2004;Stroud et al, 2011;Williams et al, 2011). In contrast, anaerobic conditions typically immobilise Sb and, again, some exceptions have been noted (Frohne et al, 2011;Hockmann et al, 2014bHockmann et al, , 2014aMitsunobu et al, 2006;Okkenhaug et al, 2012). The mechanisms behind mobilization or immobilization of As and Sb upon reducing conditions are rather complex, because changing redox conditions not only affects the speciation of As and Sb, but also the properties of their sorbents which, in turn, influences strongly As and Sb mobility.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms behind mobilization or immobilization of As and Sb upon reducing conditions are rather complex, because changing redox conditions not only affects the speciation of As and Sb, but also the properties of their sorbents which, in turn, influences strongly As and Sb mobility. For example, reductive dissolution of Fe(III) and Mn (III, IV) hydroxides can release previously bound As and Sb (Frohne et al, 2011;Hamon et al, 2004;Hockmann et al, 2014b;Lovley, 1997). In contrast, Fe(II)-induced transformation of ferrihydrite to more crystalline feroxyhyte and goethite under mild reducing conditions can immobilize Sb, likely by structural incorporation of Sb(V) into the freshly formed Fe(III) hydroxide crystal lattice (Burton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%